2009
DOI: 10.1111/j.1442-2042.2009.02311.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of female urinary incontinence in eastern Turkey

Abstract: Objectives:To evaluate the prevalence of urinary incontinence (UI) and determine risk factors for its development in women living in eastern Turkey. Methods: A cross-sectional study was conducted on 2275 women aged between 17 and 80 years. A questionnaire examining demographic characteristics, parity and pelvic organ prolapse was given. Presence and types of incontinence were examined using a validated form of the Turkish version of the urogenital distress inventory questionnaire-short form (UDI-6). Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
1
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 26 publications
9
40
1
13
Order By: Relevance
“…A study that analyzed 5,506 adults between 30 and 79 years showed that the prevalence of SUI in groups of white, black and Hispanic women were, respectively, 35.4%, 9.4%, and 14.5%. 35 Taking into account the variable age, there was no statistically significant association with SUI, a finding confirmed in a study conducted by Botleroa et al 32 We found that some studies have reported increased prevalence of UI as the subjects get older, 14,36 however, when evaluating this variable, these studies do not distinguish between different types of UI, an important detail because UUI and mixed UI have a peak prevalence after the sixth decade life. 37 An important factor that may have affected the results of the present study is that only 16.1% of the sample was over 60 years.…”
Section: Discussionsupporting
confidence: 64%
“…A study that analyzed 5,506 adults between 30 and 79 years showed that the prevalence of SUI in groups of white, black and Hispanic women were, respectively, 35.4%, 9.4%, and 14.5%. 35 Taking into account the variable age, there was no statistically significant association with SUI, a finding confirmed in a study conducted by Botleroa et al 32 We found that some studies have reported increased prevalence of UI as the subjects get older, 14,36 however, when evaluating this variable, these studies do not distinguish between different types of UI, an important detail because UUI and mixed UI have a peak prevalence after the sixth decade life. 37 An important factor that may have affected the results of the present study is that only 16.1% of the sample was over 60 years.…”
Section: Discussionsupporting
confidence: 64%
“…Fatores associados estabelecidos na literatura, como o parto e o sobrepeso, não aumentam as chances de IU em idosas ativas 2,[22][23][24][25] . Estudos demonstraram que paridade, via de parto ou realização de episiotomia não são fatores de risco para IU entre a população idosa 1,5 .…”
Section: Discussionunclassified
“…Os fatores de risco analisados foram classificados em: ginecológicos (tempo de menopausa e uso de terapia de reposição hormonal), obstétricos (número de gestações e partos normais e realização de episiotomia), clínicos (presença de hipertensão arterial e diabetes e uso de diuréticos), comportamentais (presença de constipação, consumo de cafeína e nível de atividade física), hereditários (histórico familiar e raça) e antropométricos (índice de massa corporal -IMC -e circunferência da cintura -CC). Essa ficha de avaliação tomou como base os fatores de risco para IU conhecidos na literatura 1,2,16 . A massa corporal foi determinada por meio de uma balança digital Plenna Wind MEA 07710, e a estatura, pelo estadiômetro WCS 217 cm com plataforma da marca Cardiomed.…”
Section: Métodosunclassified
See 1 more Smart Citation
“…Similarly, a study conducted in the Marmara Region by Filiz et al stated that the most common incontinence in women was the mixed type of incontinence, followed by the stress and urge types of incontinence (6). Two separate studies conducted in the Eastern and Central Anatolia Regions reported the most common incontinence type to be the stress type, followed by the urge and mixed types (23,24). These differences in prevalence of UI types are thought to have been caused by differences in the women's fertility characteristics.…”
Section: Discussionmentioning
confidence: 99%